Informed intertextuality in the conspiracy theories on Covid-19 within social media - Hashmi, U.M.; Ab Rashid, R.; Hashmi, H.A. (2021)
This paper examines the strategic construction and justifications of conspiracy theories on COVID-19 within social media. This study employed an ethnographic approach and generated data through the observation of purposively selected social media Pages, Groups, and Blogs. The six-month observation from August 2020 to January 2021 yielded 230 postings presenting propaganda against the COVID-19. The data were analyzed using intertextual analysis, drawing upon features of intertextuality. The analysis revealed that the conspiracy theories against COVID-19 are constructed upon five intertextual bases whereby the specific marked intertextuality emerged as the most used technique. The analysis also revealed that manipulation of others texts, obfuscation of intertextual sources, and exploitation of Muslim sentiments are leveraged in the construction of conspiracy theories and digital propaganda against COVID-19.